2003
DOI: 10.1097/01.ju.0000066842.45464.cc
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget Fluorescence In Situ Hybridization Assay Detects Transitional Cell Carcinoma in the Majority of Patients with Bladder Cancer and Atypical or Negative Urine Cytology

Abstract: The UroVysion FISH assay provides high sensitivity and specificity to detect transitional cell carcinoma in cytologically equivocal and negative urine samples. These results emphasize the important role of this assay in the management of bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
161
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(168 citation statements)
references
References 12 publications
5
161
0
2
Order By: Relevance
“…9,25 Urovysiont FISH is one such molecular test that has been shown to have high sensitivity and specificity for the detection of urothelial carcinoma in urine. 8,14,19,21,26 We recently observed several cases of non-urothelial carcinoma that were Urovysiont FISH-positive. Others have also observed these coincidental overlaps with non-urothelial tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,25 Urovysiont FISH is one such molecular test that has been shown to have high sensitivity and specificity for the detection of urothelial carcinoma in urine. 8,14,19,21,26 We recently observed several cases of non-urothelial carcinoma that were Urovysiont FISH-positive. Others have also observed these coincidental overlaps with non-urothelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…7 The gold standard for diagnosis and surveillance of urothelial carcinoma has traditionally been cystoscopy and urine cytology, however both have limitations. [8][9][10][11][12][13][14] Although urine cytology is excellent for detecting high-grade urothelial carcinoma (sensitivity and specificity 475%), it has a low sensitivity (20-60%) for detecting low-grade tumors. 8,[10][11][12][13][14] The low sensitivity of urine cytology, the invasiveness of cystoscopy and its limited usefulness in detecting flat and inaccessible lesions have prompted increased demand for newer, more sensitive and non-invasive tests for detection of urothelial carcinoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, abnormalities detectable by FISH may precede the evidence of carcinoma on bladder biopsies. 8,9 FISH has also shown promise in the detection of carcinomas of the breast, lung, and colon. [10][11][12][13] Multiple genetic abnormalities have been reported in Barrett's esophagus-associated adenocarcinoma and its precursors.…”
mentioning
confidence: 99%
“…Several comparative studies have demonstrated that the sensitivity of FISH is superior to that of Cytology alone. [28][29][30] Epilogue According to published reports, the happy couple has settled into a mutually satisfying relationship, each helping to complete the other. The future holds additional opportunities for spousal collaboration: many genetic events, originally identified in hematologic and mesenchymal lesions, are being discovered in a variety of carcinomas as well, particularly salivary gland carcinomas.…”
Section: Bladder Cancermentioning
confidence: 99%